Semi-autonomous avatar enabling unconstrained parallel conversations -seamless hybrid of WOZ and autonomous dialogue systems - Kawahara, Tatsuya; Muramatsu, Naoyuki; Yamamoto, Kenta; Lala, Divesh; Inoue, Koji (Advanced robotics, 2021)
Many people are now engaged in remote conversations for a wide variety of scenes such as interviewing, counseling, and consulting, but there is a limited number of skilled experts. We propose a novel framework of parallel conversations with semi-autonomous avatars, where one operator collaborates with several remote robots or agents simultaneously. The autonomous dialogue system mostly manages the conversation, but switches to the human operator when necessary. This framework circumvents the requirement for autonomous systems to be completely perfect. Instead, we need to detect dialogue breakdown or disengagement. We present a prototype of this framework for attentive listening.